Synthesis of software architectures for systems-of-systems: an automated method by constraint solving - Margarido, Milena Guessi (2017)
Systems-of-Systems (SoS) encompass diverse and independent systems that must cooperate with each other for performing a combined action that is greater than their individual capabilities. In parallel, architecture descriptions, which are the main artifact expressing software architectures, play an important role in fostering interoperability among constituents by facilitating the communication among stakeholders and supporting the inspection and analysis of the SoS from an early stage of its life cycle. The main problem addressed in this thesis is the lack of adequate architectural descriptions for SoS that are often built without an adequate care to their software architecture. Since constituent systems are, in general, not known at design-time due to the evolving nature of SoS, the architecture description must specify at design-time which coalitions among constituent systems are feasible at run-time. Moreover, as many SoS are being developed for safety-critical domains, additional measures must be placed to ensure the correctness and completeness of architecture descriptions. To address this problem, this doctoral project employs SoSADL, a formal language tailored for the description of SoS that enables one to express software architectures as dynamic associations between independent constituent systems whose interactions are mediated for accomplishing a combined action. To synthesize concrete architectures that adhere to one such description, this thesis develops a formal method, named Ark, that systematizes the steps for producing such artifacts. The method creates an intermediate formal model, named TASoS, which expresses the SoS architecture in terms of a constraint satisfaction problem that can be automatically analyzed for an initial set of properties. The feedback obtained in this analysis can be used for subsequent refinements or revisions of the architecture description. A software tool named SoSy was also developed to support the Ark method as it automates the generation of intermediate models and concrete architectures, thus concealing the use of constraint solvers during SoS design and development. The method and its accompanying tool were applied to model a SoS for urban river monitoring in which the feasibility of candidate abstract architectures is investigated. By formalizing and automating the required steps for SoS architectural synthesis, Ark contributes for adopting formal methods in the design of SoS architectures, which is a necessary step for obtaining higher reliability levels.